A Mosaic of Future Maladaptation Predicted for the Widespread Tree Nothofagus pumilio - Sekely, Jill (2026)
Nothofagus pumilio, or lenga beech, is a widespread and locally-adapted tree species endemic to South America's Patagonia region. Its diverse populations span a 2000-km-long range in the Andes Mountains, which is already experiencing adverse effects from climate change. Here the Andes contain two uncorrelated temperature and precipitation gradients, which offers a unique opportunity to evaluate how gradients drive local adaptation and conversely how changes in these gradients could lead to future maladaptation risk. We predicted climate maladaptation risk for N. pumilio populations with genomic offset. Our dataset includes 493 adult trees in 20 natural forest sites across the distribution range that were sampled with a paired-site study design, which creates the opportunity to also investigate genomic offset patterns at small spatial scales. Local climate data for both current and future projected conditions were extracted from the CHELSA online repository. We used 490 putatively-adaptive single nucleotide polymorphisms, that is, those associated with chosen climatic gradients, and assessed genomic offset using two methods: LFMM ‘genetic.gap’ and Gradient Forest. We projected risk at sampled sites and spatially across the full Argentina species distribution range, considering three possible emission scenarios and two future time periods within the 21st century, using Ensemble Means calculated from CMIP6 projections. Contrary to our expectations, our results predict a complex mosaic of heightened maladaptation risk across the landscape, with particularly high values in northern treeline and southern valley populations, across all investigated scenarios. This suggests a more complicated pattern of risk than uniformly increased risk along elevation or latitude clines. Using external evidence, we contextualize our genomic offset results and investigate possible species' responses, including how maladaptation risk could impact Patagonian forests in the future.